PREVALENCE OF HEPATITIS B IN LOCAL AREA OF DISTRICT SIALKOT, PAKISTAN - MUZAMMAL, S; ASHRAF , S; NASIR , T; ZAINAB , S; ATIF , M; IRSHAD , F; AMJAD , K (Biological and Clinical Sciences Research Journal, 2024)
Hepatitis B virus (HBV), a small encapsulated DNA virus, predominantly infects hepatocytes, causing acute and chronic liver damage. Objective: This study aimed to assess the incidence of HBV among the population of the local area of district Sialkot. Methods: A hospital-based study was conducted at Tehsil Headquarters Hospital Daska between January 2022 and May 2022. Sixty participants were registered for the study, including males and females aged 7 to 68. Data collection was performed using a standardised questionnaire. Each participant provided 5 ml of blood for an immunochromatography test. Descriptive statistics were used to analyse the data. Results: Out of the 60 participants, 20 tested reactive for HBV, with 18 males and 2 females. Most of the reactive participants were males aged between 20 and 40, and most were married. Conclusion: The findings indicate a significant incidence of HBV among males, particularly those aged 20-40 years in the district of Sialkot. These results can inform public health initiatives to prevent HBV and promote precautionary measures.